1997
DOI: 10.1029/97gl01599
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibrium of gas hydrate: Implications for the formation of hydrate in the deep sea floor

Abstract: Abstract.We calculate the solubility of methane gas over a range of pressure and temperature. The gas is dissolved in liquid water, which coexists with free gas at high temperature or solid hydrate at low temperature and high pressure. We show that solubility is significantly altered by the presence or absence of the hydrate phase. When hydrate is absent at high temperatures, our calculations reproduce experimentally observed increases in solubility with decreasing temperature. When hydrate is present, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 17 publications
6
97
0
1
Order By: Relevance
“…This mismatch arises as local pathways for fluid and gas flow are not considered in our approach. Both fluid and gas flow have a strong effect on the accumulation of gas hydrates in marine sediments and could enhance the hydrate inventory [Zatsepina and Buffett, 1997;Xu and Ruppel, 1999;Buffett and Archer, 2004;Piñero et al, 2013]. Therefore, the value of 1146 Gt C should be considered as a minimum estimate based on the in situ microbial degradation of POC.…”
Section: Discussionmentioning
confidence: 99%
“…This mismatch arises as local pathways for fluid and gas flow are not considered in our approach. Both fluid and gas flow have a strong effect on the accumulation of gas hydrates in marine sediments and could enhance the hydrate inventory [Zatsepina and Buffett, 1997;Xu and Ruppel, 1999;Buffett and Archer, 2004;Piñero et al, 2013]. Therefore, the value of 1146 Gt C should be considered as a minimum estimate based on the in situ microbial degradation of POC.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of hydrate formation has shown that free gas is not required for the formation of hydrate in seafloor sediments [Rempel and Buffett, 1997;Zatsepina and Buffett, 1997;Xu and Ruppel, 1999]. When fluids with a high concentration of dissolved methane are advected into the hydrate stability zone, a decrease in methane solubility can result in hydrate formation without the presence of free gas.…”
Section: Is Hydrate Required?mentioning
confidence: 99%
“…The pressure and temperature conditions used for the MGH stability curve were calculated using Multiflash (InfoChem Computer Services, Ltd., London, UK) assuming a gas composition of pure methane and a euxinic pore water salinity of 33.5k. Methane solubility was calculated using the methods outlined by Zatsepina and Buffett [1997] and Rempel and Buffett [1998]. In particular, for a given pressure P the methane solubility along the stability curve Ceq(T3) is first determined as a function of the stability temperature •.…”
Section: Introductionmentioning
confidence: 99%